Height adjustable high heel shoes - Foo, Clarence Chuan Wei (Nanyang Technological University, 2022)
High heel shoes are a type of shoes that are widely available in the fashion industry and are normally worn by woman. Even though the prolonged wear of high heels can bring about serious health and safety issues, there are still in high demand in the market. This is because they have the advantages of making woman appear taller, feminine, professional, and attractive. In view of this, there is a viable market for dual-function high heel shoes that can adjust their heel height according to the user’s needs.